Long-Chain Polyunsaturated Fatty Acids n-3 (n-3 LC-PUFA) as Phospholipids or Triglycerides Influence on Epinephelus marginatus Juvenile Fatty Acid Profile and Liver Morphophysiology - de Mello, Paulo H. [UNESP]; Araujo, Bruno C.; Marques, Victor H.; Branco, Giovana S.; Honji, Renato M.; Moreira, Renata G.; Rombenso, Artur N.; Portella, Maria C. [UNESP] (MDPI, 2022)
Phospholipids (PL) are membrane components composed of fatty acids (FA), while triglycerides (TG) are a main source of energy and essential FA. Polyunsaturated FA (PUFA), such as docosahexaenoic acid (DHA), and eicosapentaenoic acid (EPA), are essential for marine carnivorous fish; thus, an 8-week experiment was performed to evaluate the influence of DHA and EPA, provided as PL and TG, on the morphophysiology of Epinephelus marginatus juveniles. A basal diet was manufactured, and DHA and EPA in PL form (PL1—low amount PL2—high amount) and TG form (TG1—low amount; TG2—high amount) were added. Dusky grouper juveniles were equally distributed in 12 tanks of 20 animals each, and liver and muscle were sampled for metabolic analysis. The total hepatic lipids in PL1 and PL2 were higher when compared to the initial, TG1 and TG2 groups. Total lipids in muscle were higher in PL2 and TG1 than PL1 and TG2, respectively. Diets rich in DHA and EPA in PL and TG resulted in higher deposition of these FA in the muscle polar fraction. However, fish fed diets containing lower amounts of DHA and EPA in PL and TG stored those in the muscle neutral fraction and liver, centralizing the storage of DHA and EPA.
Keywords: docosahexaenoic acid; dusky grouper; eicosapentaenoic acid; lipid metabolism; marine phospholipid